Improvement of Quality and Patient Safety in Anaesthesia Practice in Low-Resource Settings - Nurunnabi, Abu Sadat Mohammad; Reza, Sultan; Habib, S M Ahsanul; Mohammad, Taneem; Royhan, Mir Masud; Md Zunaid; Islam, Md Ashraful; Alam, Samiul; Chakma, Shuchana (Mugda Medical College Journal, 2025)
In modern healthcare system, health policy makers, healthcare professionals and organizations, and patients are becoming more aware of the importance of promoting quality care and safety practices. In anaesthesia practice, the specialty has come a long way since its establishment in Dhaka Medical College Hospital in Bangladesh in 1950s by the house surgeons at that time. In last few decades, there had been incredible innovations in anaesthesia, such as the introduction of sevoflurane, isoflurane, propofol, the laryngeal mask airway, pulse oximetry, HDU and ICU facilities and many more. However, in Bangladesh, being a low-resource country, there are still many challenges that the specialty must meet especially in quality of care and patient safety culture. Following some recent anaesthesia-related fatalities, concerns about anaesthesia flared up among patients, health professionals and policy makers. Therefore, different healthcare organizations, both public and private, are now looking at the resiliency analysis of the anaesthesia practice in order to improve quality and patient safety to enhance patient satisfaction and trust building. This review paper aims to discuss quality improvement and patient safety in anesthesia practice and their contributing factors, standardized practices, and strategies to facilitate safety with a focus on teamwork and communication in low-resource settings. However, the review does not seek to be exhaustive or systematic, but to highlight current areas of concern and some potential solutions. Mugda Med Coll J. 2024; 7(2): 127-134